Labrundinia Fittkau, 1962 (Diptera: Chironomidae: Tanypodinae: Pentaneurini) : taxonomia e história natural de espécies do estado de São Paulo - Silva, Fabio Laurindo da (2009)
The aim this work was study species Labrundinia Fittkau, 1962 (Diptera: Chironomidae: Tanypodinae: Pentaneurini) at São Paulo State. This taxon is commonly cited in ecological studies, always in generic level. In the Neotropical region are known 10 species, however none specifically mentioned for Brazil. The sampling followed the conventional methods of benthonic studies. In laboratory the larvae were kept alive to obtain the three development phases: larva, pupa and adult. The results allowed the identification of five species*, four of which are new species and the first record of Labrundinia tenata Roback (1987) for Brazil. The species are described with their respective diagnoses. Information about species natural history of genus is presented and propels for the identification keys, for the different stages of life, are given.